(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study explores the role of local government authorities in fostering collaborative strategies that enhance synergies between agricultural digitalisation and community health management. Based on comparative case studies of local governments in Zhejiang and Sichuan provinces, the research examines how each has leveraged digital agriculture to support public health initiatives. While both governments have implemented impactful measures, Sichuan’s approach stands out as more strategic and community-orientated. In contrast to Zhejiang—where collaboration with Alibaba faced public distrust due to perceived commercial motives—Sichuan’s initiatives have gained stronger public confidence through more transparent and inclusive efforts. Sichuan’s decentralised strategy includes subsidising nutrient-rich seeds to address malnutrition, especially among children, and delivering targeted health and nutrition education to mothers and the elderly in rural areas. Despite limited resources, Sichuan’s model has benefitted from robust stakeholder engagement, involving farmer cooperatives, NGOs, and e-commerce platforms. This community-centred approach has fostered stronger synergies between agricultural innovation and public health improvement in the region.